The Role of Interpersonal Communication Between Migrant Students and Parents in Maintaining Enthusiasm for Learning : A Study of Communication Science Students of Sriwijaya University, Class of 2022) - Mutiah Mutiah; Jessica Walmar Happiness Ompusunggu (Jurnal Kaganga: Jurnal Ilmiah Sosial dan Humaniora, 2026)
Migrant students face various emotional and academic challenges due to the distance between them and their parents, which can potentially affect their enthusiasm for learning. In this context, interpersonal communication between migrant students and their parents becomes an important aspect as a source of emotional and motivational support. This study aims to understand the role of interpersonal communication between migrant students and their parents in maintaining the enthusiasm for learning of Communication Science students at Sriwijaya University, class of 2022. This study uses a qualitative approach with a phenomenological method to explore the lived experiences of migrant students in interpreting communication with their parents. Data collection was conducted through in-depth interviews with informants selected purposively. Data analysis was carried out based on the phenomenological stages referred to by Creswell and Alfred Schutz, including description of phenomena, phenomenological reduction, understanding subjective meaning, typification, and interpretation of social meaning. The results show that interpersonal communication characterized by openness, empathy, supportive attitudes, positive attitudes, and equality plays an important role in providing a sense of security, emotional support, and maintaining the enthusiasm for learning of migrant students, although there are variations in experience and not all students get the five humanistic aspects completely. The research findings confirm that the quality of communication that is built emotionally is more meaningful than the intensity of communication alone, and functions as psychological strengthening in facing the dynamics of academics and life abroad. Keyword: Interpersonal Communication, Migrant Students, Parents, Enthusiasm for Learning, Phenomenology.